Pendekatan Spasial Cellular Automata-Markov Chain Untuk Prediksi Tutupan Lahan Dan Analisis Bahaya Banjir - Bayu Muhammad Nabiil Makarim; Laju Gandharum; Ilham Badaruddin Mataburu (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Land cover change is an important environmental issue because it affects the hydrological cycle and increases the risk of flooding, especially in urban areas experiencing rapid urbanization. This study aims to predict land cover change and measure its impact on flood hazard in the Surakarta Metropolitan Area in 2030 and 2040. The method used is a combination of Cellular Automata-Markov Chain (CA-MC) to predict land cover change and flood hazard analysis methods. The results of the study show that in the 2020-2030 period, the area with the highest flood hazard increased by 3.42 hectares, while in the 2030-2040 period it increased by 1.35 hectares. This increase in flood hazard is mainly due to significant deforestation. In the period 2020-2030, deforestation of forests into built-up land and agricultural land reached 29,530.89 hectares and 6,224.76 hectares, while in the period 2030-2040, deforestation of forests into built-up land and agricultural land amounted to 25,109.73 hectares and 8,651.16 hectares. The conclusion of this study is that continued deforestation reduces the roughness of the land surface, thereby expanding the flood hazard area. Therefore, a more sustainable land management policy is needed to reduce the negative impact on the danger of flood disasters in the future.